Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Velg Dan Ban Mobil Pada Maju Jaya Wheels (MJ Wheels) di Kota Bandar Lampung - Nelson, Farrel; Efriyanti, Farida (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This research aims to find out which marketing strategies are more important for increasing sales at PD stores. Maju Jaya Wheels to face the many competitors that are coming. The informants in this research were 2 employees and 8 consumers, consumers were users of HSR rims and GT tires (single elephant), consumers were at least 20 years old and over. The analysis method uses IFAS analysis, EFAS analysis, and SWOT analysis. Based on the description and discussion that has been presented, several points can be drawn from the SWOT analysis as well as strategies that can be implemented by PD. Maju Jaya Wheels Bandar Lampung in an effort to increase sales, based on the SWOT Matrix diagram above, it is known that PD. Maju Jaya Wheels Bandar Lampung is in quadrant I, where the situation is very favorable. In this quadrant, PD. Maju Jaya Wheels Bandar Lampung has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be implemented in this condition is to support aggressive growth policies (growth oriented strategy).